Insights into the symbiotic relationship between scale worms and carnivorous sponges (Cladorhizidae, Chondrocladia). (February 2020) - Taboada, Sergi; Silva, Ana Serra; Neal, Lenka; Cristobo, Javier; Ríos, Pilar; Álvarez-Campos, Patricia; Hestetun, Jon Thomassen; Koutsouveli, Vasiliki; Sherlock, Emma; Riesgo, Ana
Abstract: Symbiotic associations between polynoid scale worms and other marine invertebrates are common, but sometimes poorly understood. Compounding this problem is the fact that polynoid systematics is largely unresolved. Here, we transfer the species originally described as Nemidia antillicola chondrocladiae Fauvel (1943), and currently synonymized with Neopolynoe acanellae (Verrill, 1881), to the species Neopolynoe chondrocladiae n. comb. This species is characterized by living in association with the carnivorous sponges Chondrocladia robertballardi Cristobo, Ríos, Pomponi & Xavier, 2015 and Chondrocladia virgata Thompson, 1873. The existence of specialized chaetae in N. chondrocladiae n. comb . and the occurrence of open galleries in the sponge, derived from a gradual overgrowth of the sponge to accommodate the worm, suggest an obligate symbiotic relationship between worm and sponge. The presence of a gravid female with relatively small oocytes (maximum diameter 56.94 ± 14.89 μm) suggests that N. chondrocladiae n. comb . is a gonochoristic broadcaster with a planktotrophic larva, a means of reproduction that would maximize the chances of this species finding new suitable hosts to colonize. We also provide a phylogenetic placement, using four genetic markers ( 18S, 28S, 16S and COI ), for N. chondrocladiae n. comb . and N . acanellae, which confirms they are two different species. In addition, we also report here the occurrence of another deep-water polynoid species in association with the carnivorous sponge Chondrocladia verticillata Topsent, 1920, from the Gulf of Mexico, and place it in a phylogeny. Highlights: Two polynoid species reported to live with two Chondrocladia carnivorous sponges. A new combination of a species of the genus Neopolynoe (Annelida, Polynoidae). We provide an updated phylogenetic framework for symbiotic polynoids. Morphological adaptations on both carnivorous sponge and polynoids are highlighted. We suggest Neopolynoe chondrocladiae n. comb. is gonochoristic and broadcaster.